Comparative Analysis of Human Development in Kazakhstan and other Eurasian Economic Union Countries - Uteubayev, Talgat (International Journal of Economics and Financial Issues, 2016)
In this paper, we consider issues of human development in Kazakhstan and in the states of the Eurasian Economic Union (EEU). The article analyzes the differences in achievements between EEU states on the human development index (life expectancy, GDP per capita, education level) and the income and standard of living (average size of salaries, pensions, minimum subsistence level, GINI coefficient and other indicators). The author noted the similarity of many problems in the field of human development, which should be taken into account in each EEU member state, and the level of integration association. Keywords: Human development, human resources, human development index, EEU JEL Classifications: F02, O31